Optimizing Laying Hen Productivity and Egg Quality through Combination of Inorganic and Organic Trace Minerals Supplementation - Atmaja, Baluh Medyabrata; Hidayatulloh, Rifqi; Ali, Muhammad Irvan; Hutabarat, Amelia Lulu Rosalin; Lestari, Wenni Meika; Agasi, Satri Yusasra; Shihah, Hanna Dzawish (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2024)
This research investigates the effects of combining inorganic trace minerals (ITMs) and organic trace minerals (OTMSs) on the performance and egg quality of laying hens. The study employed a completely randomized design (CRD), assigning 60 laying hens to three treatment groups, each consisting of 10 replications of two hens. The treatment groups were as follows: T0 = commercial feed (control), T1 = commercial feed + 500 grams/ton ITMSfeed, and T2 = commercial feed + 500 grams/ton ITMSfeed + 500 grams/ton OTMSS feed. The results revealed that the treatments did not significantly affect performance (P > 0.05). However, eggshell weight was significantly higher (P < 0.05) in the T1 and T2 groups compared to the T0 group. Eggshell thickness was significantly higher (P < 0.05) in the T2 group compared to the T0 and T1 groups. In conclusion, the addition of a combination of inorganic trace minerals (ITMs) and organic trace minerals (OTMs) to the feed can significantly improve eggshell weight and thickness but does not have a significant effect on the overall performance of laying hens.